The Influence Of Location, Word Of Mouth And Halal Label On Purchasing Decisions With Purchase Interest As An Intervening Variable - Sidik Fahmi Mukhamad; Agung Guritno (Journal of Islamic Enterpreneurship and Management, 2024)
This research analyzes "The Influence of Location, Word of Mouth and Halal Labels on Purchasing Decisions with Purchase Intention as an Intervening Variable (Study of Consumers of Fried Chicken and Tumpang Koyor Bu Yusro Salatiga)". The sample used in this research was 100 respondents from Bu Yusro Salatiga's fried chicken and fried chicken consumers. So the instruments used in this research are validity testing, reality testing, classical assumption testing, and hypothesis testing. Based on the results of the analysis that has been carried out, it can be concluded as follows. the influence of location on purchasing decisions is negative and significant, word of mouth has a positive and significant influence on purchasing decisions, halal labels have a positive and significant influence on purchasing decisions, location has a negative and significant influence on buying interest, word of mouth has a positive and significant effect on buying interest , the halal label has no effect and is not significant on buying interest, buying interest has a positive and significant effect on purchasing decisions, buying interest is not able to mediate the influence of location on purchasing decisions, buying interest is able to mediate the influence of word of mouth on purchasing decisions, buying interest is able to mediate the influence halal label on purchasing decisions.